2008
DOI: 10.1021/jf703568f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Vintage Preban Absinthe with Special Reference to Thujone, Fenchone, Pinocamphone, Methanol, Copper, and Antimony Concentrations

Abstract: Thirteen samples of authentic absinthe dating from the preban era (i.e., prior to 1915) were analyzed for parameters that were hypothesized as contributing to the toxicity of the spirit, including naturally occurring herbal essences (thujone, pinocamphone, fenchone), methanol, higher alcohols, copper, and antimony. The total thujone content of preban absinthe was found to range between 0.5 and 48.3 mg/L, with an average concentration of 25.4 ( 20.3 mg/L and a median concentration of 33.3 mg/L. The authors conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…The no-effect levels (NOEL) were in the range between 5 and 12.5 mg/kg bodyweight/day (SCF, 2003). As previously mentioned, the consumption of absinthe was unable to reach the NOEL (Lachenmeier et al, 2008). Currently, it is relatively unclear how much thujone is present in medically used wormwood preparations.…”
Section: The Medical Use Of Wormwood-a Collateral Damage Of the Absinmentioning
confidence: 99%
See 1 more Smart Citation
“…The no-effect levels (NOEL) were in the range between 5 and 12.5 mg/kg bodyweight/day (SCF, 2003). As previously mentioned, the consumption of absinthe was unable to reach the NOEL (Lachenmeier et al, 2008). Currently, it is relatively unclear how much thujone is present in medically used wormwood preparations.…”
Section: The Medical Use Of Wormwood-a Collateral Damage Of the Absinmentioning
confidence: 99%
“…These early investigations and the resultant systematic experiments with pure thujone (see below) have consistently shown that wormwood may act as a strong agent causing seizures in animals. The only issue was that the dose-response relationship was largely neglected, as later investigations have shown that the wormwood content in absinthe was so negligible that the "no-effect level" in animal experiments with additional safety factors would not have been exceeded by even excessive human absinthe ingestion (Lachenmeier et al, 2008). The most plausible hypothesis today is that absinthism was just misdiagnosed alcoholism, as ethanol alone can explain all of absinthe's alleged effects (Strang et al, 1999;Padosch et al, 2006;Lachenmeier et al, 2010).…”
Section: The Rise and Fall Of Absinthementioning
confidence: 99%
“…Trace elements, such as Cu and Pb, can be derived from the materials of the utensils used for traditional distillation (so called artisanal), including Cu pot stills (alembics) and alquitaras, distillation coils, and maturation of distilled spirits (i.e., oak wood barrels and casks) [2,3,5,8,9,[14][15][16]19,[23][24][25][26][27][29][30][31][32][33]35,36,[40][41][42]. Surface corrosion of these materials is the most common cause of Cu and Pb , and other concomitant elements being present in finished products.…”
Section: Elements In Distilled Spiritsmentioning
confidence: 99%
“…Greater attention to product authenticity and origin, quality control (QC) and suitable reference parameters of elemental composition could certainly enhance safety of these products and benefit the economy of regions dealing with the production and trade in distilled spirits. The presence of selected trace elements (i.e., Al, As, Cd, Cu, Cr, Hg, Ni, Pb, Sb, and Zn) contributes to the overall quality of these alcoholic beverages and determines their suitability and safety for consumption in view of the toxicity of certain elements above tolerable and/or allowable limits [3,5,16,19,24,25,[31][32][33][34][35]. In view of this, analysis of distilled spirits is required to assess potential health effects, while the information about concentrations of certain elements is an important parameter of the QC of these products.…”
Section: Introductionmentioning
confidence: 99%
“…Like bitters, these products' flavor chemistry have not been extensively analyzed. Gin has had some sensory and volatile profiling performed (Riu-Aumatell, Vichi, Mora-Pons, López-Tamames, & Buxaderas, 2008;Sanchez, 2011), and absinthe has been the subject of some chemical analysis that has mostly focused on quantifying concentrations of thujone and a few other components from wormwood (Lachenmeier, 2007;Lachenmeier et al, 2008). Vermouth, chartreuse, and other blended-aromatic-plant-based alcohol such as Campari have not been the subject of any published volatile or sensory studies that the authors have identified.…”
Section: Flavor Chemistry Of Bittersmentioning
confidence: 99%